High‐Mobility Sm‐Doped Bi2Se3 Ferromagnetic Topological Insulators and Robust Exchange Coupling. (14th July 2015) - Chen, Taishi; Liu, Wenqing; Zheng, Fubao; Gao, Ming; Pan, Xingchen; van der Laan, Gerrit; Wang, Xuefeng; Zhang, Qinfang; Song, Fengqi; Wang, Baigeng; Wang, Baolin; Xu, Yongbing; et al.
<x xml:space="preserve">Abstract</x> High‐mobility (SmxBi1‐x)2Se3 topological insulators (with x = 0.05) show a Curie temperature of about 52 K, and the carrier concentration and Fermi wave vector can be manipulated by intentional Te introduction with no significant influence on the Curie temperature. The origin of the ferromagnetism is attributed to the trivalent Sm dopant, as confirmed by X‐ray magnetic circular dichroism and first‐principles calculations. The carrier concentration is on the order of 1019 cm−3 and the mobility can reach about 7200 cm2 V−1 s−1 with pronounced Shubnikov–de Haas oscillations.